IMPROVING LEARNING OUTCOMES BY USING AUDIO VISUAL MEDIA IN ELEMENTARY SCHOOL STUDENTS - Acoci; Farisatma; Jannah, Nur; Matje, Irman; Agus, Jufri (Lembaga Penelitian dan Pengabdian Masyarakat FKIP UMB, 2024)
Audio visual media also helps teachers in delivering materials systematically and efficiently. With the help of this media, students can focus more on the core of learning and easily connect theory with practice. The purpose of this study is to improve student learning outcomes in the subject of science by using audio visual media in grade IV students of SD Negeri 2 Nganganaumala. This study is a PTK (classroom action research) study. Each task that will be carried out as part of the PTK in this study will use the Kemmis and MC Tanggart Spiral model which states that the task in question is one that involves a cycle of eight components including: (a) planning, (b) implementation, (c) observation, (d) reflection. The results of the study showed a significant increase in student learning outcomes after corrective actions. In the pre-cycle, the majority of students had not completed, but after cycle I, the number of students who completed increased, accompanied by an increase in average scores. This proves that the interventions implemented began to have a positive impact. In cycle II, almost all students achieved completion with a higher average score. This shows that the learning strategies implemented are effective in improving student understanding and achievement, and can be used as a reference for improving future learning.